Novel Clue to Locate Conduction Gaps in the Pulmonary Vein Isolation Ablation Line - Xie, Hai-yang; Guo, Xiao-gang; Yang, Jian-du; Chen, Yan-qiao; Cao, Zhong-jing; Sun, Qi; Ma, Jian (Frontiers in Cardiovascular Medicine, 2021)
Background: Several methods have been reported for locating the conduction gap (CG) in the pulmonary vein isolation (PVI) ablation line. However, the value of the interval between far-field atrial potential (FFP) and pulmonary vein potential (PVP) remains unknown. Methods: Consecutive patients with a CG during observation on the table after PVI were included. The PVP, FFP, and the CG location were evaluated to develop a novel algorithm to identify the CG location in the left superior pulmonary vein. The performance of this novel algorithm was prospectively tested in a validation cohort of consecutive patients undergoing repeat PVI ablation. Results: A total of 116 patients with atrial fibrillation (AF) were recruited, 56 of whom formed the validation cohort. The interval between FFP and PVP of the left superior pulmonary vein was associated with the CG location, and an interval <5 ms predicted the presence of CG in the upper portion of the ostium with a sensitivity of 92.9% and a specificity of 96.9%. In the prospective evaluation, the interval was able to correctly predict the site of CG in 89.6% of cases. Conclusions: The interval between FFP and PVP is a novel and accurate index that can be used to predict the CG location in the left superior pulmonary vein. An far-field atrial potential and pulmonary vein potential (FFP–PVP) interval value of ≥5 ms could be used to exclude a CG in the upper portion of the ostium in the majority of patients undergoing AF ablation.